The Effect of Implant–Abutment Contact Area on the Stress Generation of Bone-Level and Tissue-Level Implants - João Paulo Mendes Tribst; Nilüfer Özkara; Erik J. Blom; Cornelis Johannes Kleverlaan; Pietro Ausiello; Maria Bruhnke; Albert J. Feilzer; Amanda Maria de Oliveira Dal Piva (Applied Sciences)
Aims: This in silico study aimed to investigate the effect of implant–abutment contact surfaces on the stress generation of Morse taper implants under oblique loading. Materials and methods: Three-dimensional finite element models of Bone-Level and Tissue-Level implants were simulated with Standard and Partial contacts between the abutment and implant. The dimensional parameters followed the ISO 14801 guidelines, and an oblique load of 300 N was applied to the implants. The von Mises stress was acquired. Results: The Tissue-Level design showed a significant difference in the stress level when the connection with the implant, abutment, and screw was Partial. For the implant fixture, abutment, and screw, the Tissue-Level design showed 13% more stress in the implant, abutment, and screw when the connection was Partial. The Bone-Level design did not affect the connection and showed an overall 42% lower stress than the Tissue-Level design for the implant fixture. However, in the screw, there was a difference between the Bone-Level implants with a Standard and Partial connection. In contrast, for the Tissue-Level implant, this difference was less evident with higher stress peaks in the entire set. Conclusion: To achieve optimal outcomes, it is highly recommended to use original abutments, as they provide a more precise fit. The stress peaks were notably lower in Bone-Level implants compared to Tissue-Level implants. Furthermore, an implant–abutment connection with more contacting areas significantly reduced stress concentration, especially in Tissue-Level implant designs. By choosing well-fitting abutments, one can ensure more stable and durable implant performance with less stress.